Modeling inducible neuropathologies of the retina with differential phenotypes in organoids - Völkner, Manuela; Wagner, Felix; Kurth, Thomas; Sykes, Alex M.; Del Toro Runzer, Claudia; Ebner, Lynn J. A.; Kavak, Cagri; Alexaki, Vasileia Ismini; Cimalla, Peter; Mehner, Mirko; Koch, Edmund; Karl, Mike O. (Frontiers in Cellular Neuroscience, 2023)
Neurodegenerative diseases remain incompletely understood and therapies are needed. Stem cell-derived organoid models facilitate fundamental and translational medicine research. However, to which extent differential neuronal and glial pathologic processes can be reproduced in current systems is still unclear. Here, we tested 16 different chemical, physical, and cell functional manipulations in mouse retina organoids to further explore this. Some of the treatments induce differential phenotypes, indicating that organoids are competent to reproduce distinct pathologic processes. Notably, mouse retina organoids even reproduce a complex pathology phenotype with combined photoreceptor neurodegeneration and glial pathologies upon combined (not single) application of HBEGF and TNF, two factors previously associated with neurodegenerative diseases. Pharmacological inhibitors for MAPK signaling completely prevent photoreceptor and glial pathologies, while inhibitors for Rho/ROCK, NFkB, and CDK4 differentially affect them. In conclusion, mouse retina organoids facilitate reproduction of distinct and complex pathologies, mechanistic access, insights for further organoid optimization, and modeling of differential phenotypes for future applications in fundamental and translational medicine research.